Preferential oxidation of carbon monoxide in hydrogen-rich gas over platinum-cobalt-alumina aerogel catalysts - Kwak, C; Park, TJ; Suh, DJ (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
The performance of the platinum-cobalt catalysts in a carbon monoxide preferential oxidation (PROX) reactor was investigated for polymer electrolyte fuel cell systems. First, the PROX reaction was analyzed based on two major reactions involved in it, i.e., oxidation of carbon monoxide and the H-2-O-2 reaction. Both reactions were affected by the other reaction depending on the reaction temperature regions, but the extent of the influence is not so large. The platinum-cobalt catalysts were found to exhibit high performance in PROX of carbon monoxide in rich hydrogen as a result of catalytic synergy effect between platinum and cobalt. In order to improve such synergy effect. the catalysts were prepared by sol-gel method and subsequent supercritical drying. The platinum-cobalt catalysts prepared by the single step sol-gel procedure exhibited higher activity for PROX than the catalysts prepared by the conventional impregnation. Supercritical drying preserved the active species of platinum-cobalt phase, therefore, the platinum-cobalt composite aerogel catalyst exhibited excellent ability for the carbon monoxide removal. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: VIII METAL-SURFACES; BIMETALLIC CATALYSTS; SELECTIVE OXIDATION; CO; REMOVAL; NO; ADSORPTION; H-2; O2